Profiles and Characteristics of Balinese Cattle Breeders In The Covid-19 Era In The Village of Ayunan Badung, Bali - Ni Made Ayu Gemuh Rasa Astiti; Ni Ketut Madewi; Ni Ketut Sri Rukmini (Warmadewa University Press, 2021)
They researched the profiles and characteristics of Bali Cattle Farmers in the Covid-19 Era in the Village of Ayunan Badung Bali to know the characteristics and profiles of Balinese cattle breeders in Ayunan Village during the Covid-19 pandemic. The methods used are survey methods using primary data and secondary data. Sampling is carried out by purposive sampling questionnaire on 40 Balinese cattle breeders in the village of Ayunan and have experience raising cattle for more than three years. The study results were 77.5% of respondent breeders were in the productive age range, and 22.5% were in the age range above 64 years. Young and fertile breeders generally have a high education level, so they tend to adopt innovations and technologies more quickly. The experience of raising respondents for 21 years to 30 years is as much (35%). Long enough farming experience indicates that the respondent breeders have adequate knowledge and skills in cattle raising. Respondents' education is 2.5% not having a formal education, 25% having an elementary education, 12.5% having a junior high school education and 50% having a high school education, and 10% having tertiary education. Farmers' education level tends to influence their thinking power and acceptance of innovations and technologies. The average number of respondents' livestock ownership is 2.6 heads, caused by several factors, including the limited forage or 20% of feed, due to the determinate business capital factor 42.5% and cultivated as a side business of 37.5%. The majority of respondent breeders have their primary job as farmers/farm laborers 60%, only 5% of respondent breeders have the main job as breeders. In comparison, 35% of respondents have jobs as retirees, construction workers, laborers, agricultural extension workers, and traders. In general, cattle breeders in Bali raising cattle is a part-time job. Conclusions, profiles, and characteristics of Balinese cattle breeders in Ayunan Village, seen from the age of the breeders, have the highest percentage (62.5%) at the age of 51-64 and are classified as productive. 35% experience in farming (21-30) years, most of the education level is high school graduates (50%), average livestock ownership is 2.66 tails, the low number of livestock ownership is due to business capital 42.5% and the main occupation of respondents is 60% the farmer